DNA N6-methyladenine modifications of Acidithiobacillus ferrooxidans response to copper stress - JingQi Liu; HuangFeng Qiu; DongHua Tan; Yu Zhang; Yu Yang (PLoS ONE, 2025)
High concentrations of copper ions have long been recognized as a key factor limiting the efficiency of bioleaching due to the metal toxicity to microorganisms. In order to identify new determinants of copper resistance, we assessed the impact of different copper ion concentrations on the bioleaching model organism Acidithiobacillus ferrooxidans . Furthermore, we employed 6mA IP-seq technique to evaluate changes in the 6mA methylation levels of A. ferrooxidans under two conditions: iron oxidation and sulfur oxidation, both under copper stress. The results indicated that as the concentration of copper ions in the growth environment increased, the copper toxicity significantly inhibited the growth of A. ferrooxidans . The maximum tolerable copper ion concentration for iron-grown and sulfur-grown A. ferrooxidans was found to be 100 mM. Under 100 mM Cu 2+ exposure, 184 and 242 differentially methylated genes were identified in the iron oxidation and sulfur oxidation A. ferrooxidans , respectively(P < 0.01). From the Kyoto Encyclopedia of Genes and Genomes (KEGG) functional analysis, under iron oxidation conditions, 130 differentially methylated genes were annotated and mapped into 7 KEGG pathways, while under sulfur oxidation conditions, 188 differentially methylated genes were annotated and mapped into 4 KEGG pathways (P < 0.05). Several differentially methylated genes were found to be associated with the following responses to copper stress: iron-sulfur oxidation acceleration, amino acid synthesis, and activation of the RND-type efflux system, polypeptide-based copper resistance systems, and metal ATPases to expel copper ions. In summary, the 6mA methylation levels in A. ferrooxidans change under copper stress, and these changes are widely present in various copper resistance genes. This study reveals a novel copper resistance mechanism in A. ferrooxidans , providing new insights for enhancing bioleaching efficiency and demonstrating significant implications for advancing biometallurgy.